Virtual occlusal definition for orthognathic surgery. Issue 3 (March 2016) - Liu, X.J.; Li, Q.Q.; Zhang, Z.; Li, T.T.; Xie, Z.; Zhang, Y.
Abstract: Computer-assisted surgical simulation is being used increasingly in orthognathic surgery. However, occlusal definition is still undertaken using model surgery with subsequent digitization via surface scanning or cone beam computed tomography. A software tool has been developed and a workflow set up in order to achieve a virtual occlusal definition. The results of a validation study carried out on 60 models of normal occlusion are presented. Inter- and intra-user correlation tests were used to investigate the reproducibility of the manual setting point procedure. The errors between the virtually set positions (test) and the digitized manually set positions (gold standard) were compared. The consistency in virtual set positions performed by three individual users was investigated by one way analysis of variance test. Inter- and intra-observer correlation coefficients for manual setting points were all greater than 0.95. Overall, the median error between the test and the gold standard positions was 1.06 mm. Errors did not differ among teeth ( F = 0.371, P > 0.05). The errors were not significantly different from 1 mm ( P > 0.05). There were no significant differences in the errors made by the three independent users ( P > 0.05). In conclusion, this workflow for virtual occlusal definition was found to be reliable and accurate.